Diagnostic and Prognostic Utility Compared among Different Sepsis Scoring Systems in Adult Patients with Sepsis in Thailand: A Prospective Cohort Study - Prat Pairattanakorn (2022)
Background: The diagnostic and prognostic utility of various sepsis scores varied among different cohorts and settings. Methods: A prospective cohort study in adult patients with sepsis at Siriraj Hospital (Bangkok, Thailand) was conducted during January to July 2019. The performance of sepsis assessments, including systemic inflammatory response syndrome (SIRS) score, sequential organ failure assessment (SOFA) score, quick sepsis-related organ failure assessment (qSOFA) score, modified early warning score (MEWS), and national early warning score (NEWS), for sepsis detection and mortality prediction were compared with agreement between 2 infectious disease (ID) specialists to determine their sepsis and septic shock status as the reference standard. Results: Among the 470 subjects included in this study, 206 patients (43.8%) were determined by 2 ID specialists to have sepsis. Systemic inflammatory response syndrome≥2, qSOFA≥2, and NEWS≥5 yielded the highest sensitivity (93.2%), specificity (81.3%), and accuracy (72.6%), respectively, for detecting sepsis. The SIRS≥2 had the highest sensitivity (97.8%), whereas qSOFA≥2 had the highest specificity (61%) and accuracy (69.7%) for predicting mortality among sepsis patients. Receiver operating characteristic (ROC) curve showed MEWS to have the highest discriminatory power for sepsis detection (area under the ROC curve [AUROC], 0.79; 95% confidence interval [CI], 0.74-0.83), whereas SOFA had the highest discriminatory power for predicting hospital mortality (AUROC, 0.76; 95% CI, 0.69-0.79). Conclusions: The NEWS≥5 and qSOFA≥2 were the most accurate scoring systems for sepsis detection and mortality prediction, respectively. Each scoring system is useful for different specific purposes relative to early detection and mortality prediction in sepsis patients.